IDDF2018-ABS-0111 Safety and efficacy of treatment with once-daily LEDIPASVIR/SOFOSBUVIR (90/400 MG) for 12 weeks in genotype 1 hcv-infected patients with severe renal impairment. (June 2018) - Lawitz, Eric; Landis, Charles S; Maliakkal, Benedict J; Bonacini, Maurizio; Ortiz-Lasanta, Grisell; Zhang, Jie; Mogalian, Erik; De-Oertel, Shampa; Osinusi, Anu O; Brainard, Diana M; McHutchison, John G; Sze Man Yip, Christina; et al.
Abstract : Background: Despite higher concentrations of the primary circulating sofosbuvir (SOF) metabolite, GS-331007, in patients with severe renal impairment (RI), retrospective case series and claims database analyses have suggested substantial use of ledipasvir (LDV)/SOF in this population with no untoward effects described. The current study evaluated the safety, efficacy, and pharmacokinetics (PK) of LDV/SOF (90/400 mg) once-daily for 12 weeks in patients with genotype (GT) 1 HCV-infection and severe RI. Methods: Treatment naive or experienced patients with or without compensated cirrhosis and creatinine clearance (CLcr). Results: Of the 18 patients, the majority were male (67%), 10 (56%) were African-American, 8 (44%) had BMI≥30 kg/m2 and mean (range) CLcr at baseline was 24.9 (9.0–39.6) mL/min. In terms of liver disease characteristics, all 18 had GT1 HCV infection (14 GT1a and 4 GT1b), 14 (78%) were treatment naive, and 2 (11%) had cirrhosis. All patients completed 12 weeks of LDV/SOF treatment. There were no early discontinuations nor any on-treatment virologic failures. The SVR12 rate is 100% (18/18). Plasma concentrations of the terminal SOF metabolite GS-3310007 were approximately 6 fold higher than in the LDV/SOF Phase 3 trials. SOF and LDV concentrations were similar to those with normal, mild or moderate RI. The most common adverse events (AEs) were fatigue (22%), headache (22%), and hyperkalemia (22%). Six serious AEs were reported among 4 patients (22%), including 2 renal events; no SAEs related to study drugs. There were no treatment-related cardiac AEs, including bradycardia, and no meaningful changes in QTc intervals or other parameters. Conclusions: Treatment with LDV/SOF (90/400 mg) for 12 weeks in genotype 1 patients with and without cirrhosis and severe renal impairment resulted in 100% SVR12 rate. The regimen was safe and well-tolerated with no treatment discontinuations and no treatment-related SAEs. (no table selected) (No Image Selected) Co-Author Disclosure Status.